PEMIDANAAN ANGGOTA MILITER PELAKU PERSETUBUHAN SESAMA JENIS (STUDI PUTUSAN NOMOR 231-K/PM.II-8/AU/XII/2020) - Muhammad Ramadhion Prastopo (Reformasi Hukum Trisakti, 2022)
These actions are punishable by both disciplinary action and criminal action. For instance, a military member who engages in same-sex sexual activity (gay) may face punishment as a Military Criminal, which includes the following: "refuses or deliberately disobeys an official order, or arbitrarily exceeds such an order" and is subject to the threat of intentional disobedience, as stated in Article 103 Paragraph (1) of the KUHPM. The Panel's judgment in this matter was not correct because it only imposed a sentence of one article, namely Article 103 paragraph (1) of the Criminal Procedure Code, even though the defendant's actions fulfilled the three articles charged, namely Article 294 paragraph (2) 1st Criminal Code, Article 281 1st Criminal Code and Article 103 paragraph (1) the Criminal Procedure Code. the defendant's actions have tarnished the military's image, so the Panel of Judges should have imposed a principal sentence that is heavier than 8 (eight) months or the Judge could maximize the sentence of Article 103 paragraph (1) of the Criminal Procedure Code, namely imprisonment for two years and four months and an additional penalty in the form of dismissal from military service.